Does research matter in residency applications? A single institution's experience. Issue 3 (May 2016) - Larson, Eric; Wojcik, Jonathan; Cannada, Lisa K.
Abstract : Background: Orthopaedic surgery has become one of the most competitive specialties for medical students to pursue. With increasing numbers of well-qualified applicants applying into the field, it has become essential for students to distinguish themselves, and one effective way of doing so is through research involvement. Methods: Saint Louis University (SLU) graduates from 2010-2015 who successfully matched into orthopaedic surgery were contacted and asked about their involvement in research, what field that research was in, whether it led to any publications or presentations, and which faculty member oversaw the project. Results: Between 2010 and 2015, 41 students matched into orthopaedic surgery from SLU out of a total of 42 who had applied, yielding a 97.6% match rate. Sixty-eight percent (26/38) of the graduates who responded to our survey took part in a total of 45 orthopaedic surgery research projects. This research resulted in 19 publications and 28 presentations. Thirty-three projects were done through the SLU Department of Orthopaedics and 12 projects were done at an outside facility. Of the 12 graduates who responded to the survey and denied orthopaedic research, eight took part in research projects through other departments. Conclusions: SLU's match rate into orthopaedics over the last 6 years (97.6%) is significantly above the national average for the same period of time (75.6%). Thirty-four of 38 (89.5%) of our graduates were engaged in research during medical school, which is well above the reported national average for medical students (57%). We believe this strong research involvement accounts for our high match rate into orthopaedics.